The epistemological roots of structural realism: Models and representation in international relations theory - Morales Giraldo, Juan Francisco (2020)
The text explores some basic ideas about the epistemology behind the theory of Structural Realism, or Neorealism, by Kenneth Waltz. First, the problem of descriptive interpretation of theories, particularly in the discipline of International Relations, as well as certain critical conceptions that arise from this logic. Second, the formal structure of the theoretical programs is analyzed in general, with an emphasis on the theoretical structure of Structural Realism. The notion of the duality of international political phenomena is described as an element central to the core of empirical laws and principles of theory, defining its purpose and establishing its scope and limitations. Finally, the last section explores the predictive potential of international relations theories, elaborating a critical approach to these issues from the theory itself. Finally, the conclusions consider the contribution of Waltz's general theory on the way of thinking theories and their importance for the discipline of Relations Internationals.